The Role of Early Growth Response Family Members 1–4 in Prognostic Value of Breast Cancer - Hao, Leiyu; Huang, Fengru; Yu, Xinqian; Xu, Bujie; Liu, Yan; Zhang, Yan; Zhu, Yichao (Frontiers in Genetics, 2021)
Early growth response family members (EGRs), EGR1-4, have increasingly attracted attention in multiple cancers. However, the exact expression patterns and prognostic values of EGRs in the progress of breast cancer (BRCA) remain largely unknown. The mRNA expression and prognostic characteristics of EGRs were examined by the Cancer Genome Atlas (TCGA), Oncomine and Kaplan-Meier plotter. Enrichment analyses were conducted based on protein-protein interaction (PPI) network. The Tumor Immune Estimation Resource (TIMER) database and MethSurv were further explored. The protein expression of EGR1 in BRCA was measured by western blotting and immunohistochemistry. The migration of mammary epithelial cells was determined by Boyden chamber assay. The transcriptional levels of EGR1/2/3 displayed significantly low expression in BRCA compared to that in normal tissues, while EGR4 was shown adverse expression pattern. Survival analysis revealed up-regulated EGR1-4 were remarkably associated with favorable relapse-free survival (RFS). A close correlation with specific tumor-infiltrating immune cells (TIICs) and several CpG sites of EGRs were exhibited. Immunohistochemistry assays showed that the protein expression of EGR1 was remarkably downregulated in BRCA compared to that in paracancerous tissues. The migration of MCF10A mammary epithelial cells was increased after the silence of EGR1 by siRNA transfection. This study provides a novel insight to the role of EGRs in the prognostic value of BRCA.